2020
DOI: 10.1002/etc.4927
|View full text |Cite
|
Sign up to set email alerts
|

Use of Postregistration Monitoring Data to Evaluate the Ecotoxicological Risks of Pesticides to Surface Waters: A Case Study with Chlorpyrifos in the Iberian Peninsula

Abstract: Chemical monitoring data sets such as those provided by the implementation of the Water Framework Directive (WFD) offer opportunities to evaluate the ecological risks of pesticides under large spatiotemporal scales and to evaluate the protectiveness of the current prospective risk‐assessment framework. As a case study, we used the monitoring data set for the insecticide chlorpyrifos to perform a probabilistic risk assessment for Iberian surface‐water ecosystems. The specific objectives of the study were 1) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…Bifenthrin is often found in the San Francisco Bay and surrounding watershed up to 9.9 ng/L and has been found in estuaries within China up to 291 ng/L, both of which encompass the LC 10 values [59,60]. In the USA and globally, chlorpyrifos has been detected within estuaries and surface waters up to 96.0 µg/L, concentrations that encompass the LC 10 values found in this study [61][62][63]. Myclobutanil has also been detected in global estuarine surface waters at levels close to the LC 10 values found in this study [64].…”
Section: Resultssupporting
confidence: 60%
“…Bifenthrin is often found in the San Francisco Bay and surrounding watershed up to 9.9 ng/L and has been found in estuaries within China up to 291 ng/L, both of which encompass the LC 10 values [59,60]. In the USA and globally, chlorpyrifos has been detected within estuaries and surface waters up to 96.0 µg/L, concentrations that encompass the LC 10 values found in this study [61][62][63]. Myclobutanil has also been detected in global estuarine surface waters at levels close to the LC 10 values found in this study [64].…”
Section: Resultssupporting
confidence: 60%
“…Particularly, the most used OPPs in the Sele River Plain were chlorpyrifos and dimethoate, with about 27 and 4 tons sold per year, respectively [ 50 ]. Many studies reported a high predominance of chlorpyrifos and dimethoate in several areas of southern Europe [ 6 , 51 , 52 ], including Italy [ 53 , 54 , 55 ], which led to them being identified as hazardous substances for water biodiversity in Mediterranean ecosystems [ 51 , 56 , 57 ]. Therefore, according to the last agriculture census by ISTAT (2010), in line also with the current European regulations, such as the Water Framework Directive (WFD) [ 58 ], and considering the current bibliography [ 3 , 5 , 10 , 16 , 23 , 27 , 30 , 34 , 59 ], the OPPs investigated in the study area were: diazinon, dimethoate, malathion, chlorpyrifos, pirimiphos-methyl, fenitrothion, methidathion, tolclofos-methyl, and parathion ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both pesticides are included in the list of priority substances of the Water Framework Directive (WFD) (EC, 2011) and are highly relevant for European surface waters as well as globally due to their widespread use and ecological risks (Arenas-Sánchez et al, 2019;Huang et al, 2020;Rico et al, 2021). As an acetylcholinesterase inhibitor, chlorpyrifos disturbs the signal transmission in the nervous system, causing impairment in mobility (Sharma et al, 2012) and eventually mortality, particularly on aquatic arthropods such as D. pulex (Cuppen et al, 2002;Daam et al, 2008).…”
Section: Introductionmentioning
confidence: 99%